Modeling Antarctic tides in response to ice shelf thinning and retreat - Rosier, S.H.R.; Green, J.A.M.; Scourse, J.D.; Winkelmann, R. (Hoboken, NJ : Blackwell Publishing Ltd, 2014)
Tides play an important role in ice sheet dynamics by modulating ice stream velocity, fracturing, and moving ice shelves and mixing water beneath them. Any changes in ice shelf extent or thickness will alter the tidal dynamics through modification of water column thickness and coastal topography but these will in turn feed back onto the overall ice shelf stability. Here, we show that removal or reduction in extent and/or thickness of the Ross and Ronne-Filchner ice shelves would have a significant impact on the tides around Antarctica. The Ronne-Filchner appears particularly vulnerable, with an increase in M2 amplitude of over 0.5 m beneath much of the ice shelf potentially leading to tidally induced feedbacks on ice shelf/sheet dynamics. These results highlight the importance of understanding tidal feedbacks on ice shelves/streams due to their influence on ice sheet dynamics. publishedVersion